2014
DOI: 10.4103/1319-3767.129474
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemoradiation in locally advanced rectal cancer: A comparison of bolus 5-fluorouracil/leucovorin and capecitabine

Abstract: Purpose:To compare the acute toxicities, pathologic response, surgical margins, downstaging, local control, disease-free survival (DFS), and overall survival (OS) in locally advanced rectal cancer patients with preoperative radiotherapy (RT) with either concurrent bolus 5-fluorouracil (5-FU)/leucovorin (LV) or capecitabine (CA).Materials and Methods:Sixty patients who presented to our department with a diagnosis of locally advanced rectal cancer were treated with surgery following preoperative RT with either c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…There was no significant heterogeneity between the studies ( P = .54), and the fixed-effects model was used. The data in all the 10 studies [15,2129] were available for the analysis of pCR. There were 1408 patients in the capecitabine group and 1382 patients in the 5-FU group in this meta-analysis, and the pCR rates were 19.53% and 15.48%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant heterogeneity between the studies ( P = .54), and the fixed-effects model was used. The data in all the 10 studies [15,2129] were available for the analysis of pCR. There were 1408 patients in the capecitabine group and 1382 patients in the 5-FU group in this meta-analysis, and the pCR rates were 19.53% and 15.48%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The improvements in magnetic resonance and ultrasound endoscopy allows more accurate preoperative staging can be achieved, [20] and accordingly develop clinical studies with different regimens of neoadjuvant chemoradiotherapy. [15,2129] Ten studies of 5-FU and capecitabine efficacies of neoadjuvant CRT in LARC were compared in this meta-analysis. All 10 studies have shown that preoperative CRT using capecitabine and 5-fluouracil is feasible and improves the pCR rate.…”
Section: Introductionmentioning
confidence: 99%
“…The result could be misinterpreted to mean that capecitabine has weaker systemic effects than 5-FU, which differs from the results of previous studies. In general, capecitabine not only shows better oncologic outcomes than 5-FU at a systemically effective dose as an adjuvant treatment (1,250 mg/m 2 twice daily), but its oncologic superiority continues at a lower dose (825 mg/m 2 twice daily) as a radiosensitizer for CRT [9, 10]. Because the results in our study may have statistical bias due to the small number of patients in the EF group, further study including a larger number of patients is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment choice for CRC varies according to tumor location and stage at diagnosis. [ 20 21 ] Surgery is the most common treatment for early-stage (stage I and II) CRC. For patients with stage III CRC, surgery is frequently followed by short chemotherapy (approximately 6 months) to decrease the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%